Pemberdayaan Keluarga dalam Pemantauan Tumbuh Kembang Balita di Desa Penfui Timur - Diyan Maria Kristin; Hasri Yulianti (Rena Cipta Mandiri, 2026)
Regular monitoring of under-five growth and development is essential for early identification of growth faltering, developmental delay, and nutritional problems. Families are the primary observers of children’s daily changes; however, the use of the Maternal and Child Health Handbook, growth charts, and age-appropriate stimulation is not always consistent. This community service activity aimed to strengthen family capacity to monitor the growth and development of children under five in Penfui Timur Village. A participatory empowerment approach was applied through coordination with community health volunteers, interactive education, demonstrations on interpreting growth charts, exercises to identify age-specific developmental milestones, case discussions, and preparation of family follow-up plans. Evaluation was conducted descriptively using attendance records, pre- and post-activity questions, practice observation checklists, and participant reflection. The activity was carried out in March 2026, involved families of children under five and volunteers from Posyandu in Penfui Timur. Participants actively engaged in the sessions, improved their understanding of growth parameters, became more capable of recognizing warning signs, and expressed readiness to conduct regular recording and monitoring at home and at Posyandu. Practice-based family empowerment may strengthen early detection and continuity of child growth and development monitoring.